Science and literature in the italian 20th century - Battistini, Andrea (Revista de Letras, 2011)
This essay intends to present a panoramic study about the relationship between the natural sciences and the literature in Italy, from the last years of the 19th century to the last years of the 20th century. We will demonstrate that the scientific theme occupies large space in the poetry and in the narrative of authors like Carducci, D’Annunzio, Pirandello and Marinetti. In the last paragraphs, we will analyze the italian science fiction which, less important than in other countries, acquires more relevance in the second half of the 20th century.